The Impact of the COVID-19 Pandemic on Exports – The Perspective of Polish Companies - Sylwia TALAR; Małgorzata DZIEMBAŁA; Joanna KOS-ŁABĘDOWICZ (Communications of International Proceedings, 2021)
The COVID-19 pandemic has the potential to influence a company’s exports, but its final impact may differ depending on particular factors and circumstances. The aim of this paper is to determine the impact of the COVID-19 pandemic on firms' exports (performance and prospects) across different types of economic activities and industries. We put forward a general research question of whether sectoral or industrial business specificity matters when it comes to the impact of the pandemic on businesses’ performance. To find the answer and achieve our aim, several detailed hypotheses were formulated. These are verified with the use of statistical methods. The study is based on firm level data collected using a survey conducted between the 14th and the 21st July 2021 on Polish companies. The main findings of this study imply that export performance across industries may be determined more by other factors than by demand and supply shocks caused by the pandemic. Moreover, the distinction between production, services, retail and wholesale may be a key differentiator of the influence of the pandemic on export performance and prospects.
Keywords: Export; Trade; COVID-19; Pandemic; Industries; Economic Activity; Polish Companies